ANALISIS KEBUTUHAN DAN SEBARAN GURU GEOGRAFI SMA/MA NEGERI DI PADANG PARIAMAN TAHUN 2021 - 2026 - Nur Azizah; Khairani khairani (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
This study aims to describe the needs and distribution of geography teachers in 2021 – 2026 presented in tabular form. The method used in this research is descriptive qualitative, including purposive sampling, techniques and data collection tools conducted by 3 ways of observation, questionnaire and documentation. The result of the study 1) the number of geography teacher needs of SMA/MA Negeri in Padang Pariaman regency amounted to 36 teachers while existing teachers reached 47 geography teachers, resulting in an excess of geography teacher needs as many as 11 geography teachers 2) the distribution of geography teachers SMA/MA Negeri in Padang Pariaman regency has not been evenly distributed in 9 districts because there is still a gap between existing teachers and the need for the teacher.